2017
DOI: 10.1653/024.100.0325
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Markers for the Determination ofCoptotermes formosanus×Coptotermes gestroi(Isoptera: Rhinotermitidae) F1 Hybrids

Abstract: Coptotermes gestroi (Wasmann) and Coptotermes formosanus (Shiraki) represent the most widely distributed subterraean termites (Rhinotermitidae) in the world. The wide distribution of C. gestroi has only come to light in the past decade, as numerous junior synonyms for this tropical termite have been resolved. With C. gestroi found in the equatorial zone, and C. formosanus in the subtropics and warm temperate regions, the distributions of these two invasive termites currently overlap in only three locations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Since 2013, simultaneous dispersal flight events were observed in Florida (Chouvenc et al, 2015(Chouvenc et al, , 2017b) and heterospecific mating behavior were observed, as AST males readily initiated tandem with females of FST (Chouvenc et al, 2015). From such pairings, hybrid colonies from the two possible mating combinations (♀AST × ♂FST and ♀FST × ♂AST) were successfully established in the laboratory, showing that there were no pre-zygotic barriers for the production of a viable F 1 hybrid brood (Chouvenc et al, 2015(Chouvenc et al, , 2017a. Hybrid colonies after 1 year of foundation showed relatively high hybrid vigor by displaying faster colony growth compared to colonies founded with conspecific pairs of FST and AST (Chouvenc et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2013, simultaneous dispersal flight events were observed in Florida (Chouvenc et al, 2015(Chouvenc et al, , 2017b) and heterospecific mating behavior were observed, as AST males readily initiated tandem with females of FST (Chouvenc et al, 2015). From such pairings, hybrid colonies from the two possible mating combinations (♀AST × ♂FST and ♀FST × ♂AST) were successfully established in the laboratory, showing that there were no pre-zygotic barriers for the production of a viable F 1 hybrid brood (Chouvenc et al, 2015(Chouvenc et al, , 2017a. Hybrid colonies after 1 year of foundation showed relatively high hybrid vigor by displaying faster colony growth compared to colonies founded with conspecific pairs of FST and AST (Chouvenc et al, 2015).…”
Section: Introductionmentioning
confidence: 99%